2020
DOI: 10.3390/biom10101380
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Survival and Pro-Apoptotic Effects of 6-Shogaol on SW872 Human Liposarcoma Cells via Control of the Intrinsic Caspase Pathway, STAT-3, AMPK, and ER Stress

Abstract: Notably, 6-Shogaol, a bioactive natural substance, has anticancer effects on many types of tumors. Up to date, the anticancer effect and mode of action of 6-Shogaol on liposarcoma are not known. In this study, we investigated whether 6-Shogaol inhibits the growth of SW872 and 93T449 cells, two different human liposarcoma cell lines. Of note, 6-Shogaol inhibited the growth of SW872 and 93T449 cells without affecting that of normal 3T3-L1 preadipocytes. Specifically, 6-Shogaol further induced the apoptosis of SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…These findings strongly imply that inhibition and/or knockdown of STAT-3 could be a therapeutic target against cancers in which abnormal STAT-3 activation and expression are problematic. Of interest, it has been recently demonstrated that STAT-3 inhibition induces apoptosis of different types of fibrosarcoma cells [ 42 ]. Of further note, in a recent study, we have demonstrated that STAT-3, but not STAT-5 (another STAT-family members) is substantially expressed and phosphorylated in SW872 cells and its expression and phosphorylation play pivotal roles in the cell survival and apoptosis inhibition based on the facts that STAT-3 gene silencing leads to the cell growth inhibition and apoptosis induction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings strongly imply that inhibition and/or knockdown of STAT-3 could be a therapeutic target against cancers in which abnormal STAT-3 activation and expression are problematic. Of interest, it has been recently demonstrated that STAT-3 inhibition induces apoptosis of different types of fibrosarcoma cells [ 42 ]. Of further note, in a recent study, we have demonstrated that STAT-3, but not STAT-5 (another STAT-family members) is substantially expressed and phosphorylated in SW872 cells and its expression and phosphorylation play pivotal roles in the cell survival and apoptosis inhibition based on the facts that STAT-3 gene silencing leads to the cell growth inhibition and apoptosis induction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, it has been recently demonstrated that STAT-3 inhibition induces apoptosis of different types of fibrosarcoma cells [ 42 ]. Of further note, in a recent study, we have demonstrated that STAT-3, but not STAT-5 (another STAT-family members) is substantially expressed and phosphorylated in SW872 cells and its expression and phosphorylation play pivotal roles in the cell survival and apoptosis inhibition based on the facts that STAT-3 gene silencing leads to the cell growth inhibition and apoptosis induction [ 42 ]. In this study, tetrandrine treatment markedly reduces STAT-3 expression and phosphorylation in SW872 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cell count analysis was carried out in triplicates. Data are mean ± standard error (SE) of three independent experiments [48].…”
Section: Nile-red Stainingmentioning
confidence: 99%
“…6-shogaol ( Figure 4I ), a natural phenolic compound, is the major active ingredient in Zingiber officinale Roscoe. Studies have found that 6-shogao possesses antiemetic, anti-inflammatory, antioxidant, and anticancer activities, as well as cardiovascular and neuroprotective effects ( Kou et al, 2018 ; Chen et al, 2020 ; Yadav and Jang 2020 ). Jin et al found that 6-shogaol exerts cellular antioxidant activity by mediating Nrf2 signaling through activation of the JNK pathway ( Kim and Jang 2016 ).…”
Section: Introductionmentioning
confidence: 99%